Kinematics Singularity Solution and Simulation Analysis of Redundant Manipulator based on Screw Theory - Xinhong Feng (Jixie chuandong)
The solution and simulation analysis of the singularity configurations within its workspace of the seven axis cooperative KUKA manipulator is presented. Firstly， the manipulator kinematics model is constructed and the DH parameter is obtained. Secondly， the Jacobian matrix is computed based on screw theory and the screw reciprocity method is used to find the singularity configurations. Finally， the dexterity of end reference point of robot is analyzed based on manipulability index and the minimum singular value index by means of the Robotics Toolbox. The analysis results reveals that there are four singular conditions of the seven axis cooperative KUKA robot within its workspace， and the simulation results verifies the correctness of the analysis， and it lays a foundation for subsequent manipulator singularity avoidance arithmetic research.